Strengths and Weaknesses of Strategic Health Purchasing for Universal Health Coverage in Rwanda - Stella M. Umuhoza; Sabine F. Musange; Alypio Nyandwi; Agnes Gatome-Munyua; Angeline Mumararungu; Regis Hitimana; Alexis Rulisa; Parfait Uwaliraye (Taylor & Francis Group, 2022)
ABSTRACTIn the context of scarce resources and increasing health care costs, strategic purchasing is viewed as a key mechanism to spur countries' progress toward universal health coverage (UHC), by using limited resources more effectively. We applied the Strategic Health Purchasing Progress Tracking Framework to examine the health purchasing arrangements in three health financing schemes in Rwanda-the Community Based Health Insurance (CBHI) scheme, the Rwanda Social Security Board (RSSB) medical scheme, and performance-based financing (PBF). Data were collected from secondary and primary sources between September 2020 and March 2021.The objective of the study was to identify areas of progress in strategic purchasing that can be built on, and to identify areas of overlap, duplication, or conflict that limit progress in strategic purchasing to advance UHC goals. This study found that Rwanda has made progress in many areas of strategic purchasing and has a strong foundation for building further. However, some overlaps and duplication of functions weaken the power of purchasers to improve resource allocation, incentives for providers, and accountability. In addition, some of the policies within the purchasing functions could be made more strategic. In particular, open-ended fee-for-service payment in the CBHI scheme not only threatens the scheme's financial sustainability but also imposes a high administrative burden. Better alignment and integration of contracting, incentives, and information system design to provide timely and relevant information for purchasing decisions would contribute to more strategic health purchasing and ensure that Rwanda's health sector achievements are sustained and expanded.